Effects of NSC in different organs and at different growth stages on the yield of oil peony Fengdan with different ages - Wang, Chengzhong; Ma, Xiaoyi; Li, Qingkui; Hu, Yonghong; Yang, Ji; Song, Zhiping (Frontiers in Plant Science, 2023)
Nonstructural carbohydrates (NSC) as resource reserves of plants play important roles in energy supply for normal growth and reproduction under environmental stress. The yield of perennial crops is mainly determined by the carbohydrate production and allocation in the current growth season, but also influenced by the re-allocation of NSC reserves. However, the contribution of NSC to crop yield is still debate. Fengdan (Paeonia ostii) is a variety of oil Peony newly developed in China, the factors influencing its yield have not been soundly elucidated. In order to examine the effects of tree age and NSC on yield, we investigated the variations of biomass, soluble sugars, starch and NSC at organ and whole tree levels in the dormant and ripening stages of 4-, 6-, and 8- years old Fengdan population in two years (2020 and 2021). The results showed that the biomass, yield (seed biomass), soluble sugars, starch and NSC reserve of Fengdan at whole tree level increased with the increase of age. Although there were not consistent correlations between soluble sugars, starch and NSC storage and yield among the plant with different ages, Fengdan showed allometric growth relationships between the accumulations of soluble sugars, starch, and NSC and yield and biomass (standardized major axis analyses slope b ≠ 1). The root had the highest NSC allocation in both the dormant stage and the fruit ripening stage, suggesting root was the most important NSC storage structure. Compared with that in root, NSC accumulation in stem decreased significantly from dormancy stage to fruiting stage, hinting stem was the key structure supplying energy (NSC) for the spring growth and blossom Fengdan from dormancy. These findings together suggest that tree age and the size of NSC reserves in dormant stems has significant effects on the growth and yield of Fengdan.